Mycobacterium bovis BCG Surface Antigens Expressed under the Granuloma-Like Conditions as Potential Inducers of the Protective Immunity - Yingyu Chen; Lia Danelishvili; Sasha J. Rose; Luiz E. Bermudez (International Journal of Microbiology)
Bovine tuberculosis (bTB) is a highly transmissible infection and remains of great concern as a zoonosis. The worldwide incidence of bTB is in rise, creating potential reservoir and increased infection risk for humans and animals. In attempts to identify novel surface antigens of Mycobacterium bovis as a proof-of-concept for potential inducers of protective immunity, we investigated surface proteome of M. bovis BCG strain that was cultured under the granuloma-like condition. We also demonstrated that the pathogen exposed to the biologically relevant environment has greater binding and invasion abilities to host cells than those of bacteria incubated under regular laboratory conditions. A total of 957 surface-exposed proteins were identified for BCG cultured under laboratory condition, whereas 1,097 proteins were expressed under the granuloma-like condition. The overexpression of Mb1524, Mb01_03198, Mb1595_p3681 (PhoU1 same as phoY1_1), and Mb1595_p0530 (HbhA) surface proteins in Mycobacterium smegmatis leads to increased binding and invasion to mucosal cells. We also examined the immunogenicity of purified recombinant proteins and tested M. smegmatis overexpressing these surface antigens for the induction of protective immunity in mice. Significantly high levels of specific IgA and IgG antibodies were observed in recombinant protein immunized groups by both inhalation and intraperitoneal (IP) routes, but only IP delivery induced high total IgA and IgG levels. We did not detect major differences in antibody levels in the M. smegmatis group that overexpressed surface antigens. In addition, the bacterial load was significantly reduced in the lungs of mice immunized with the combination of inhaled recombinant proteins. Our findings suggest that the activation of the mucosal immunity can lead to increased ability to confer protection upon M. bovis BCG infection.